Answer:
It looks really good! Lol, I wish I could art ✌
Answer:
you still need help
Step-by-step explanation:
Answer:
f(-3)= -3
Step-by-step explanation:
We are given the function:
f(x) = 2x+3
and asked to find f(-3). Essentially, we want to find f(x) when x is equal to -3.
Therefore, we can substitute -3 for each x in the function.
f(x)= 2x+3 at x= -3
f(-3)= 2(-3) +3
Solve according to PEMDAS: Parentheses, Exponents, Multiplication, Division, Addition and Subtraction
Multiply 2 and -3.
f(-3) = (2*-3) +3
f(-3)= (-6)+3
Add -6 and 3.
f(-3)= (-6+3)
f(-3)= -3
If f(x)= 2x+3, then<em> f(-3)= -3</em>
I don't why you put -+ but I will go ahead and assume that it is -2.
4-+6
I think it is saying 4 - positive 6 but I'm guessing.
Answer: 1400 packages
Step-by-step explanation:
1150+1200+1900+1350 divided by the 4 day interval means and average of:
1400 packages per day